(untitled) (Journal of Fatima Jinnah Medical University, 2018)
Introduction: Echinococcosis or Hydatid disease is caused by larvae, which are the metacestode stage of the tapeworm Echinococcus. Disease is widely spread especially in sheep growing areas. Rural population handling with animals usually suffers from the disease. Four species are recognized and belong to the family Taeniidae. Taenia Ecchinococcus involves human beings as an accidental host. Liver is affected most commonly. Lungs are effected less commonly as compared to liver but enormous size of cyst markedly compromises normal pulmonary function. Routine chest x-rays can indicate presence of a cyst and CT scan can give a considerable support in diagnosis. Objective: The cyst needs a definite surgical management. Because most of the cyst in lungs are enormous in size, surgical management is not simple. To evaluate the success of surgical intervention along with its safety we conducted this study. Methods: Gulab Devi hospital is a tertiary care hospital dealing with cardiothoracic diseases. During Jan 2007-Dec 2009 we operated upon 72 cases of Hydatid lung disease. All patients were worked up for surgical fitness and only those were excluded who were declared unfit for surgery or anesthesia. Results: Male female ratio was 40/32 and most of them belonged to age group 30-50 yrs. 56 patients were symptomatic at presentation while in rest cyst was found on routine radiography. Multiple unilateral cysts were seen in 15 and 12 had bilateral cysts. Ruptured hydatid encountered in 24. Cystectomy and obliteration of space was done in 58, lobectomy in 10 and wedge resection in 4 patients. Postoperative course was uneventful in 60, complications in 11 and 1 mortality. Conclusion: It is concluded that surgery for hydatid lung disease is safe in majority of cases as it involves very little morbidity/ mortality and provides complete cure of the disease.